KUALITAS LINGKUNGAN PENGASUHAN DAN PERKEMBANGAN SOSIAL EMOSI ANAK USIA BALITA DI DAERAH RAWAN PANGAN - Hastuti, Dwi; Fiernanti, Dinda Yourista Ike; Guhardja, Suprihatin (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2011)
Psychosocial Stimulation and Social-Emotional Development of Under Five Children in the Food Insecurity Area Abstract The objective of this research was to analyze family resources allocation, psychosocial stimulation, and social emotional development of child aged 2-5 years in Banjarnegara’s food insecure area. This research involved 300 families that were selected randomly. Data collected by observation and interview. Psychosocial stimulation were measured by using the HOME instrument, while social emotional development were determined by using Vineland Social Maturity Scale instrument. Data was analyzed by descriptive and correlation analysis. Results showed that psychosocial stimulations were categorized as low. Childrens social emotional development correlated significant with mother’s education level, children’s age, family’s expenditures, and psychosocial stimulation. Psychosocial stimulation was the most associated factor to the children’s social-emotional developments. Therefore, psychosocial stimulations was very important aspect to be improved. Psychosocial stimulations were correlated to mother’s educational level, children’s age, family’s expenditures, allocation for food and nonfood expenditures, and allocation for educational matter.